Search 73,319 tutors
FIND TUTORS
Ask a question
0 0

solve for x:3(6x+3)-2(x-3)=0

Tutors, please sign in to answer this question.

1 Answer

Crista:
 
The first thing you should do is eliminate the parentheses by distributing the factor outside, as follows:
 
3*6x+3*3-2x+6=0
18x  + 9  -2x+6=0
 
Next, collect like terms and simplify:
 
18x-2x+9+6=0
16x+15=0
 
Now, Subtract 15 from both sides to isolate the x term:
 
16x+15-15=0-15
16x          =  -15
 
Finally, divide both sides by 16:
 
(16x)/16  =  -15/16
    x         =  -15/16
 
Hope this helps.
 
George T.